Government Investment and Government Expenditure on Regional Original Income of Central Java Province 2021 - 2023 - Rif'an Frandika Adi Ghufron; Zulfikar Zulfikar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the effect of corporate investment and government expenditure on regional original revenue (Pendapatan Asli Daerah or PAD) in Central Java Province during the period of 2021 to 2023. The research specifically tests the hypotheses that (1) corporate investment has a positive and significant effect on regional revenue, and (2) government expenditure has a positive and significant effect on regional revenue. Using a multiple linear regression model, the analysis incorporates classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity, alongside statistical evaluations such as R, adjusted R², F-tests, and t-tests, processed using SPSS. The study uses secondary data obtained from government publications and official investment reports at the provincial level. Findings indicate that both corporate investment and government expenditure have a statistically significant positive impact on regional revenue in Central Java. The model shows a relatively high adjusted R² value, confirming a strong explanatory power of the independent variables on the dependent variable. Multicollinearity diagnostics show acceptable Variance Inflation Factor (VIF) values, indicating that multicollinearity is not a concern in the model. These results underscore the vital role of both investment and public expenditure in driving fiscal performance at the regional level.